2019
DOI: 10.1186/s13075-019-1919-6
|View full text |Cite
|
Sign up to set email alerts
|

Skin thickness score as a surrogate marker of organ involvements in systemic sclerosis: a retrospective observational study

Abstract: Background Previous studies have shown the relationship between higher skin thickness score and the existence of organ involvements in systemic sclerosis (SSc). Here, we firstly investigated the correlation between skin thickness score and quantitative measurements of each organ involvement in Japanese patients with SSc. Methods All Japanese SSc patients hospitalized to our clinic for initial evaluation of SSc were selected. Skin thickness was evaluated by modified Rodn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…Several studies support these findings ( 16 – 18 ): in particular, Matsuda et al. ( 18 ) described the relationship between skin and lung fibrosis along three aspects: chronological (both develop in the first few years of the natural course of SSc), pathohistological (both share some part of the mechanism that lead to the fibrosis), and therapeutic (B cell-targeting therapy improve skin fibrosis and lung functions). We did not found a correlation between the degree of skin and esophageal involvement.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies support these findings ( 16 – 18 ): in particular, Matsuda et al. ( 18 ) described the relationship between skin and lung fibrosis along three aspects: chronological (both develop in the first few years of the natural course of SSc), pathohistological (both share some part of the mechanism that lead to the fibrosis), and therapeutic (B cell-targeting therapy improve skin fibrosis and lung functions). We did not found a correlation between the degree of skin and esophageal involvement.…”
Section: Discussionmentioning
confidence: 92%
“…We used skin thickness as a way to measure skin fibrosis. Skin thickening is one of the earliest manifestations of scleroderma; and is one of the most widely used measures in the clinical trials [ 14 17 ]. Several studies have demonstrated that the extent of skin involvement directly correlates with internal organ involvement and prognosis in scleroderma patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the mRSS is the main measure of outcome in dcSSc with less than 5 years from the onset of the first symptom different from Raynaud's phenomenon. Thus, any biomarker, able to correlate with mRSS, may be considered as a surrogate outcome measure for severity and mortality in patients with dcSSc [37,62,63].…”
Section: Discussionmentioning
confidence: 99%